Untangling Classroom Positionings: An Instrumental Case Unpacking Positioning Theory in Mathematics Education. (3rd April 2022) - Edelen, Daniel; Bush, Sarah B.; Schmidt, Ashley; Fulton, Tandrea; Kebreab, Lybrya; Rutledge, Treshonda
ABSTRACT: In this paper, we aim to untangle positioning theory (Davies & Harré, 1990) and its implications for the field of mathematics education research, considering both existing use and potential use. Specific theoretical assumptions of positions or positionings in the context of learning mathematics are outlined. In this paper, a classroom-based instrumental case study illuminates examples of how students are positioned within their mathematical experiences as a means to understand some of the factors that affect how students come to exist within mathematical spaces and how classroom-based positionings impact students' opportunities to engage in learning. Our goal is to present positioning theory as a potential tool for how our teaching practices impact students' experiences in mathematical spaces. We present a moment-by-moment analysis, from an ethnographic perspective of the case, to clearly demonstrate how positioning theory may be utilized for both research and practice within mathematics education research. Implications for methodology and positioning theory through an ethnographic perspective are shared.